Gram negative septicaemia diagnosed on peripheral blood smear appearances. Issue 1 (January 1994) - Fife, A; Hill, D; Barton, C; Burden, P
Abstract : Buffy coat smears from febrile patients may contain visible bacteria and therefore detect bacteraemia before conventional blood cultures become positive. However, it is unusual to see micro-organisms in an otherwise untreated peripheral blood smear. The case of a febrile neutropenic patient is reported. A Wright's stained peripheral blood smear contained bacterial elements, thus making earlier diagnosis of septicaemia and identification of the causative bacterium possible.